Describing the Internal Control of Agrivet Stores in Pagadian City - Marlon B. Paguia; Eligen H. Sumicad; Mylene P. Alfanta; Queenie E. Sta. Maria; Jea B. Semilla; Krieshelle Ann A. Looc (Jurnal Inovasi Akuntansi (JIA), 2026)
Purpose: Internal control serves as a vital foundation in ensuring efficiency, accountability, and risk management for micro enterprises such as Agrivet Stores. This research aims to describe the internal control practices of Agrivet Stores in Pagadian City, focusing on the effectiveness of control environment, control activities, risk assessment, information and communication, and monitoring, as well as the challenges and coping strategies of store owners. Method: Using a mixed-methods approach, the study combined survey questionnaires and in-depth interviews to gather both quantitative and qualitative data. Findings: Findings show that internal control practices are generally rated as high with a mean of 3.10 and standard deviation of 0.694. Qualitative results revealed challenges such as limited staffing, weak documentation, inventory losses, and risks of misappropriation, which owners addressed through strategies like improving recording practices, adopting simple technological systems, documenting losses, segregating duties, strengthening security, and enforcing employee accountability. Implications: Overall, the study underscores the importance of adaptive internal control practices in small-scale enterprises, offering insights that can guide resource management, efficiency, and asset protection in the agricultural retail sector.